Legal Protection for Foreign Students at Universitas Negeri Padang Based on the Principles of Certainty and Justice in Islamic Law - Nurjanah Nurjanah; Al Ikhlas; Engkizar Engkizar; Cisia Padila (Jurnal Kawakib, 2025)
Legal protection and certainty for foreign students in higher education have become global concerns. Even former U.S. President Donald Trump's policy on the presence of foreign students at Harvard University sparked international controversy. This highlights the importance of legal protection and certainty for international students in all countries that serve as destinations for higher education. Universitas Negeri Padang (UNP) has hosted foreign students since 2016, and their numbers continue to grow in line with the university’s rising popularity and global ranking. The presence of international students must be supported by guaranteed legal protection and certainty so that they can pursue their studies under a clear legal framework. This study aims to explore the forms of legal protection provided to foreign students at Universitas Negeri Padang, Indonesia. The research adopts a qualitative case study approach. Data were collected through in-depth interviews with eleven informants, including the head of the International Office and foreign students from Malaysia and Myanmar, selected through purposive sampling. To strengthen the interview data, the researcher also conducted document analysis using a normative juridical approach relevant to the research topic. The data were analyzed thematically using Miles and Huberman's interactive model. The findings reveal that legal protection for foreign students is implemented in several forms: (i) ensuring safety, security, and health; (ii) providing excellent administrative services throughout the academic process; and (iii) guaranteeing the right to practice their faith and religion. These findings serve as a preliminary reference for future researchers to further investigate this topic in different contexts and objectives. As a globally reputable university, Universitas Negeri Padang has fulfilled the standards, requirements, and key elements of legal protection in accordance with both global and Islamic principles.